The deepening of the integration process in the EU as a response to the challenges of political and economic crisis - O. M. Rudik (Aspekti Publìčnogo Upravlìnnâ, 2015)
The article deals with the proposals recently put forward by government ministers of Germany and France S. Gabriel and E. Macron on radically deep integration of eurozone Member-states. A stronger eurozone should be the core of a deepened EU. Ministers offer to upgrade eurozone architecture by creating its budget which would have its own revenues, strengthening the executive powers through the creation of the eurozone grouping within the European Parliament and position of a member of the European Commission, which could embody this stronger eurozone focusing on fiscal policy but also on growth, investment and job creation. The Ministers noted that the EU have to find and implement the means by which European general interest will stop appearing different from national interest of Member states. It is concluded that the deepening of European integration, updating EU by further reforming its legal and institutional systems, is beneficial for Ukraine because the success of domestic reforms in Ukraine, the vector of development of our state and its civilization choice will depend largely on both the success of a project of united Europe as a whole and its key elements – internal market and a single European currency.